Deciphering long-term coastal dynamics using IR-RF and ESR dating: a case study from Médoc, south-west France - Kreutzer, Sebastian; Duval, Mathieu; Bartz, Melanie; Bertran, Pascal; Bosq, Mathieu; Eynaud, Frédérique; Verdin, Florence; Mercier, Norbert (Quaternary geochronology, 2018)
A proper understanding of local palaeoenvironmental histories is an iterative process. Previously settled interpretations suddenly demand a reconsideration triggered by findings from sites not accessible before. The coastline of the Médoc area in south-west France faced considerable recent erosion, providing new valuable insights into the history of the local Holocene and Pleistocene deposits; mainly of estuarine, lacustrine and aeolian origin. In the framework of the project LITAQ for reconstructing the coastal history of the Aquitaine basin, new recently outcropped sediment profiles have been investigated. To establish the chronological framework, for the first time optically stimulated luminescence (OSL) on quartz, infrared radiofluorescence (IR-RF) on K-feldspar were applied in conjunction with multiple-centres electron spin resonance (ESR) dating on quartz. Our approach combines routine luminescence dating application with methodological investigations, with a focus on IR-RF and ESR dating. IR-RF and ESR ages are consistently older than the OSL ages, presumably due to insufficient bleaching, however, they are consistent within 2σ. Our study confirms that the investigated area is covered by Holocene sands, following Pleistocene colluvial and aeolian sandy deposits mainly deposited in a periglacial context during MIS 8 and MIS 10. The base of the profiles appears to consist of interglacial estuarine deposits, probably from the Holsteinian (MIS 11), supporting the theory of a progressive replacement of a tide-influenced marsh by a peaty fresh-water pond during that period. Finally, IR-RF and multiple-centres ESR dating can be considered as valuable tools to decipher Middle Pleistocene landscape dynamics.